2021
DOI: 10.3390/microorganisms9030485
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mapping Reveals Complex Regulatory Activities of BfmR in Pseudomonas aeruginosa

Abstract: BfmR is a response regulator that modulates diverse pathogenic phenotypes and induces an acute-to-chronic virulence switch in Pseudomonas aeruginosa, an important human pathogen causing serious nosocomial infections. However, the mechanisms of action of BfmR remain largely unknown. Here, using chromatin immunoprecipitation followed by high-throughput sequencing (ChIP-seq), we showed that 174 chromosomal regions of P. aeruginosa MPAO1 genome were highly enriched by coimmunoprecipitation with a C-terminal Flag-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…The comparison to this set extracted from 22 previous studies and composed of 59 known binding sites concerning 21 RRs showed that the vast majority were effectively retrieved, often resulting in very highly enriched peaks (Figure S2), further validating our approach. We then compared our results to the previously reported ChIP-seq studies on RRs for which we detected binding sites (PhoB, GacA, GltR, PhoP, CzcR, DsbR and BfmR) (Bielecki et al, 2015;Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yang et al, 2021;Yu et al, 2021). Here again, there was a strong overlap in detected binding sites between the DAP-seq data and the six different ChIP-seq studies, as well as highly similar identified DNA motifs (Figure S3).…”
Section: Dap-seq Allows the Investigation Of The Tcss Regulatory Networksupporting
confidence: 61%
See 3 more Smart Citations
“…The comparison to this set extracted from 22 previous studies and composed of 59 known binding sites concerning 21 RRs showed that the vast majority were effectively retrieved, often resulting in very highly enriched peaks (Figure S2), further validating our approach. We then compared our results to the previously reported ChIP-seq studies on RRs for which we detected binding sites (PhoB, GacA, GltR, PhoP, CzcR, DsbR and BfmR) (Bielecki et al, 2015;Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yang et al, 2021;Yu et al, 2021). Here again, there was a strong overlap in detected binding sites between the DAP-seq data and the six different ChIP-seq studies, as well as highly similar identified DNA motifs (Figure S3).…”
Section: Dap-seq Allows the Investigation Of The Tcss Regulatory Networksupporting
confidence: 61%
“…Peak lists from ChIP-seq experiments with PhoB, GacA, CzcR, GltR, PhoP, DsbR and BfmR were used to retrieve all peak summit locations (Bielecki et al, 2015;Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yang et al, 2021;Yu et al, 2021). Peak summit positions were averaged between replicates and used to infer gene targets using the genome-wide promoter regions defined above with the Intersect tool from BEDTools (Quinlan and Hall, 2010) on the corresponding genomes: PAO1 (Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yu et al, 2021) or PA14 (Bielecki et al, 2015;Yang et al, 2021). For DNA motif determination, peak regions were extended by 50bp on each side of the summits and retrieved using the GetFastaBed tool from BEDTools (Quinlan and Hall, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peak lists from ChIP-seq experiments with PhoB, GacA, CzcR, GltR, PhoP, DsbR and BfmR were used to retrieve all peak summit locations ( 23–28 ). Peak summit positions were averaged between replicates and used to infer gene targets using the genome-wide promoter regions defined above with the Intersect tool from BEDTools ( 49 ) on the corresponding genomes: PAO1 ( 24–26 , 28 ) or PA14 ( 23 , 27 ). For DNA motif determination, peak regions were extended by 50 bp on each side of the summits and retrieved using the GetFastaBed tool from BEDTools ( 49 ).…”
Section: Methodsmentioning
confidence: 99%